2017
DOI: 10.3390/min7020031
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Zinc Sulfide Concentrate during the Roasting at Microwave Frequencies

Abstract: Abstract:Microwave technology has a potential application in the extraction of zinc from sulphide ores, knowledge of the dielectric properties of these ores plays a major role in the microwave design and simulation for any process. The dielectric properties of zinc sulfide concentrate for two different apparent densities-1.54 and 1.63 g/cm 3 -have been measured by using the resonance cavity perturbation technique at 915 and 2450 MHz during the roasting process for the temperature ranging from room temperature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…In all cases, penetration depth is reduced as temperature increases. This result is in agreement with observations made of similar materials by other researchers [15,25]. As expected, the penetration depth is higher in the case of lower carbon content due to lower loss factor values that allow deeper penetration of microwave energy into the sample.…”
Section: Dielectric Properties As a Function Of Carbon Contentsupporting
confidence: 93%
See 1 more Smart Citation
“…In all cases, penetration depth is reduced as temperature increases. This result is in agreement with observations made of similar materials by other researchers [15,25]. As expected, the penetration depth is higher in the case of lower carbon content due to lower loss factor values that allow deeper penetration of microwave energy into the sample.…”
Section: Dielectric Properties As a Function Of Carbon Contentsupporting
confidence: 93%
“…As expected, higher dielectric properties are observed for more compacted samples, since the amount of air is reduced in the mixture. Previous studies made on similar materials within narrow density ranges (i.e., from 1.54 to 1.63 g/mL in [25]) concluded that temperature has a greater effect on dielectric properties than apparent density. The presented results show that, if a wide range of densities is considered, the effect on the dielectric properties can be comparable to the effect of temperature rise.…”
Section: Dielectric Properties As a Function Of Compaction Densitymentioning
confidence: 97%
“…Moreover, the dielectric properties of powder samples were measured using the resonant cavity perturbation method. [20,31] Therefore, the dielectric properties of the ber can be obtained by the resonant cavity perturbation method. The principle is to measure the resonance frequency and quality factor before and after the ber is loaded, so that the dielectric constant is calculated based on the difference between the resonance frequency and the quality factor.…”
Section: Methodsmentioning
confidence: 99%